Relationship of incidence of radix entomolaris and C-shaped canal on mandibular molars using CBCT: A multi-center study - Mohamed Khazin, Sobrina; Omar, Siti Hajar; Kamaruzaman, Marlena; Abd Ghani, Huwaina; Deepthi, Mandava; Kamarudin, Diyana; Baharin, Safura Anita; Chakravarthy, Vinayak Pishipati Kalyan (International Journal of Allied Health Sciences, 2024)
PURPOSE: This study aimed to explore the co-occurrence of RE and CSC on FM and SM, respectively, and their association with gender, race, and geographical location in Malaysian population. METHODS: 1015 CBCT images of permanent mandibular molars from Malaysian patients were collected retrospectively from 7 dental schools in Peninsular Malaysia. The CBCT images were analysed by one researcher from each dental school, trained with CBCT technology. The presence and absence of RE and CSC on FM and SM respectively were scored as yes/no. Sociodemographic data were recorded. RESULTS: The prevalence of FM with RE was 21.2% and SM with CSC was 37.9%. The co- occurrence of RE and CSC on the same quadrant was 6.5% (OR=1.497, p=0.014). Female, Chinese, and samples from Eastern of Peninsular Malaysia were associated with CSC on SM (p<0.05). CONCLUSION: The increased appearance of CSC on SM when RE is present on FM makes it imperative for clinicians to be vigilant during examination and diagnosis to prevent potential endodontic mishaps. With improved understanding of root and canal anatomy, there will be increased awareness of potential challenges and limitations of root canal treatment procedures.